An Ever Closer Union? The Nationalisation of Political Parties in Switzerland, 1991–2015. Issue 1 (21st February 2016) - Bochsler, Daniel; Mueller, Sean; Bernauer, Julian
Abstract: The contribution of this research note is a systematic description of levels of party nationalisation in Switzerland, using results from the elections to the Swiss National Council between 1991 and 2015. Party nationalisation is understood as the territorial homogeneity of a party's electoral performance and measured using the inverted and standardised Gini index. Our results indicate a trend towards more nationalisation in the Swiss party system over the time period covered, and distinct patterns for single parties. The SVP and the GLP have made big leaps towards stronger nationalisation, with the former closing in on the levels of the SP and the FDP, while the CVP remains a weakly nationalised party, considering its size.